Measurement uncertainty evaluation at mass calibration - Zakharov, I. P.; Botsiura, O. A.; Patsenko, O. (NNC Institute of metrology, 2020)
Example 9.3.1.1 of JCGM-S1 “Mass calibration” is analyzed, which describes the comparison in air of reference and calibrated weights having the same nominal mass. JCGM-S1 compares uncertainty evaluation procedures based on the GUM uncertainty framework and the Monte Carlo method. The article uses the procedure developed by the authors and consists in decomposing the measurement model into a Taylor series of the second order taking into account the kurtoses of the distributions of input quantities. To facilitate the calculations, the finite increment method is used. To find expanded uncertainty, the kurtosis method is used. Good agreement between the results obtained by the proposed method and the result obtained by the Monte Carlo method is shown.
Keywords: measurement uncertainty; calibration; nonlinear model equation; kurtosis method; weight